a) 18.17−3.6.7
= 18.17 - 18 . 7
= 18 ( 17 - 7 )
= 18 . 10 = 180
b) 54−6.(17+9)
= 54 - 102 - 54
= - 102
c) 33.(17−5)−17.(33−5)
= 33. 17 - 33. 5 - 17 .33 + 17 . 5
= 17 . 5 - 33 . 5
= 5 ( 17 - 33 )
= 5. (-16)
= - 80
a) 18.17 - 3.6.7
= 18.17 - 18.7
= 18.(17 - 7 )
= 18 . 10
= 180
b) 54 - 6.(17 + 9)
= 6.9 - 6.17 + 6.9
= (6.9 - 6.9) - 6.17
= 0 - 6.17
= 0 - 102
= -102
c) 33.(17 - 5) - 17.(33 - 5)
= 33.17 - 33.5 - 17 . 33 - 17.5
= 33.(17 - 17) - 5.(33 - 17 )
= 33. 0 - 5.16
= 0 - 80
= -80
a, 18.17 - 3.6.7 = 18.17 - 18.7
= 18 ( 17 - 7 )
= 18 . 10
= 180
b, 54 - 6( 17 + 9 ) = 6.9 - 6 ( 17 + 9 )
= 6 ( 9-17-9 )
= 6 . (-17 )
= -102
c, 33.(17-5 ) -17 ( 33-5 ) = 33. 17 - 33.5 - 17.33 + 17 . 5
= 17.5 - 33.5
= 5 ( 17 - 33 )
= 5 . ( -16 )
= -80
18x17-18x7
18(17-7)
18x10
180
b)54-(6x9)+17
54-54+17
1+17
18
c)33-(17+5)
33-32
1
a, 18.17 - 3.6.7 = 6.3.17 - 3.6.7 = 6.3.(17 -7) = 18.10 = 180
b, 54 - 6.(17 + 9) = 54 - 6. 26 = 6.9 - 6.26 = 6.(9 - 26) = 6.(-17) = -102
c, 33.(17 - 5) - 17.(33 - 5) = 33.17 - 33.5 - 17.33 - 17.5 = 33.5 - 17.5 = 5.( 33 - 17) = 5. 6 = 30
a, 18.17 - 3.6.7 = 18.17 - 18.7 = 18. ( 17-7 ) = 18.10 = 180
b, 54 - 6. ( 17+9 ) = 9.6 - 6. 26 = 6. ( 9-26 ) = 6. (-17) = -102
c, 33. ( 17-5 ) - 17. ( 33-5 ) = 33.17 - 33.5 - 17.33 + 17.5
= ( 33.17 - 17.33 ) + ( -33.5 + 17.5 )
= 0 + 5. ( -33+17 )
= 0 + 5. (-16)
= 0 + (-80)
= -80
a) 18.17 - 3.6.7
= 18.17 - 18.7
18.(17 - 7) = 18.10 = 180
b)54 - 6.(17 + 9)
= 9.6 - 6.26 = 6.(9 - 26)
= 6.(-17) = -102
c)33.(17 - 5) - 17.(33 - 5)
= 33.17 - 33.5 - 17.33 + 17.5
= (33.17 - 17.33) + (-33.5 + 17.5)
= 0 + 5.(-33 + 17)
= 5.(-16) = -80
=